Istiqamah Dalam Al-Qur’an: Kajian Tematik Atas Keserasian Ayat (Qs. Hud [11]: 112; Qs Fussilat [41]: 30-32; Qs Al-Ahqaf [46]: 13-14) - Yogi Juliansyah; Edi Hermanto (CV. ITTC INDONESIA, 2026)
This article examines the concept of istiqamah in the Qur’an through a thematic interpretation (maudhu’i) approach, emphasizing the harmony of meaning across verses as developed by M. Quraish Shihab. The primary problem addressed in this study is how the Qur’an constructs a comprehensive concept of istiqamah through the integration of messages in several different verses. This study employs a qualitative method with a library research design and a thematic approach, analyzing QS. Hud [11]: 112, QS. Fussilat [41]: 30–32, and QS. Al-Ahqaf [46]: 13–14. Data were collected from primary sources, including the Qur’an and classical commentaries, supported by other relevant literature. The results indicate that these verses possess a harmonious relationship and form a complete conceptual pattern: beginning with the command to remain steadfast, followed by guarantees of tranquility and angelic protection, and concluding with promises of salvation and happiness in the hereafter. This harmony reaffirms that istiqamah is not merely behavioral consistency but a continuous process reflecting the depth of faith and obedience to Allah. Consequently, this study concludes that the concept of istiqamah in the Qur’an is harmoniously structured and holds strong relevance in the formation of individual character and social life.